THE STUDY OF MODIFIERS IMPACT ON THE PROCESS OF PELLETIZING HARDWOOD WASTE - Kurka, Roman (Forestry, Forest, Paper and Woodworking Industry, 2024)
A process for pelletizing hardwood wherein the particulated wood is treated with a starch, wax emulsion and lignosulfonate prior to pelleting is disclosed.